Draft Five Year Plan (2012-17) and Annual Plan (2012-13) Volume-III State Planning Commission Government of Uttarakhand - Planning Commission (Planning Commission, 2012)
Major Headwise (Summary) , GN Statements A , Schemewise Approved Outlay , Physical Targets , Externally Aided Projects , Centrally Sponsored Schemes , Tribal Sub Plan(TSP) (Financial) , Tribal Sub Plan(TSP) (Physical) , Scheduled Caste Sub-Plan(SCSP) (Financial) , Scheduled Caste Sub-Plan(SCSP) (Physical) , Flagship Programme
Draft Five Year Plan (2012-17) & Annual Plan (2012-13) Volume-III
Government of Uttarakhand